Nonorthogonality and κ-Dependence Eccentricity of Polarized Electromagnetic Waves in CPT-Even Lorentz Violation - Thiago Prudêncio; Humberto Belich (Advances in High Energy Physics)
We discuss the modified Maxwell action of a KF-type Lorentz symmetry breaking theory and present a solution of Maxwell equations derived in the cases of linear and elliptically polarized electromagnetic waves in the vacuum of CPT-even Lorentz violation. We show in this case that the Lorentz violation has the effect of changing the amplitude of one component of the magnetic field, while leaving the electric field unchanged, leading to nonorthogonal propagation of electromagnetic fields and dependence of the eccentricity on κ-term. Further, we exhibit numerically the consequences of this effect in the cases of linear and elliptical polarization, in particular, the regimes of nonorthogonality of the electromagnetic wave fields and the eccentricity of the elliptical polarization of the magnetic field with dependence on the κ-term.